2019
DOI: 10.1186/s13287-019-1297-7
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the cargos and functions of exosomes derived from six cardiac cell types: a systematic review

Abstract: Exosomes are bilayer membrane vesicles with cargos that contain a variety of surface proteins, markers, lipids, nucleic acids, and noncoding RNAs. Exosomes from different cardiac cells participate in the processes of cell migration, proliferation, apoptosis, hypertrophy, and regeneration, as well as angiogenesis and enhanced cardiac function, which accelerate cardiac repair. In this article, we mainly focused on the exosomes from six main types of cardiac cells, i.e., fibroblasts, cardiomyocytes, endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 73 publications
0
62
0
2
Order By: Relevance
“…Exosomes equip a unique and powerful carrier for cells to deliver a variety of bioactive components and promote intercellular communication. Recently, exosomes from many stem cells, including mesenchymal stem cells (MSCs) (Lai et al, 2010), embryonic stem cells (ESCs) , cardiac progenitor cells (CPCs) (Barile et al, 2018), induced pluripotent stem cells (iPSCs) (Adamiak et al, 2018), and adipose-derived stem cells (ADSCs) (Xu et al, 2019) have been well investigated for their cardiac repair potency in several types of cardiovascular diseases, such as myocardial ischemia/reperfusion injury or myocardial infarction. Among these cell types, iPSCs is the most promising candidate for therapeutic applications because they can be generated from the patient's own somatic cells, possess extensive cell-renewal capability and potentially provide a variety of cell types that can be re-administered to the patient (Zhu et al, 2018).…”
Section: Exosomes From Stem Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exosomes equip a unique and powerful carrier for cells to deliver a variety of bioactive components and promote intercellular communication. Recently, exosomes from many stem cells, including mesenchymal stem cells (MSCs) (Lai et al, 2010), embryonic stem cells (ESCs) , cardiac progenitor cells (CPCs) (Barile et al, 2018), induced pluripotent stem cells (iPSCs) (Adamiak et al, 2018), and adipose-derived stem cells (ADSCs) (Xu et al, 2019) have been well investigated for their cardiac repair potency in several types of cardiovascular diseases, such as myocardial ischemia/reperfusion injury or myocardial infarction. Among these cell types, iPSCs is the most promising candidate for therapeutic applications because they can be generated from the patient's own somatic cells, possess extensive cell-renewal capability and potentially provide a variety of cell types that can be re-administered to the patient (Zhu et al, 2018).…”
Section: Exosomes From Stem Cellsmentioning
confidence: 99%
“…The therapeutic delivery of exosomes through the circulation system by using miRNAs mimics or synthetic exosomes as cargos and vehicles have been widely studied. Exosomes from CPCs (CPC-EXOs), ADSCs (ADSC-EXOs), MSCs (MSC-EXOs) or other stem cells have indicated positive results in the field of ischemic heart repair, including stimulation of angiogenesis and suppression of apoptosis (Xu et al, 2019). Because of the specific miRNA and cytokines in the cargo of CPC-EXOs, the therapeutic effect of CPC-EXOs is reported to be better than that of CPCs and MSC-EXOs (Barile et al, 2018;Xu et al, 2019).…”
Section: Exosomes From Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This form of intercellular communication allows horizontal transfer of genetic information between stem and resident adult cells via extracellular vesicles. Several studies have demonstrated that the exosomes of cardiac cells may be vital to their capacity for renewal [6,17].…”
Section: Paracrine Factors; Small Signalling Molecules and Growth Facmentioning
confidence: 99%
“…A standardized/optimal method of isolating and purifying exosomes from cells of interest is yet to be achieved [7,45]. It has been suggested that the capacity for CPCs to heal the damaged myocardium may be related to exosomal signalling [17,46]. Manipulation of these extracellular vesicles may offer an alternative, or complementary treatment to implantation.…”
Section: Unanswered Questions -A Summary Of Areas Where More Study Ismentioning
confidence: 99%